2022
DOI: 10.1111/rda.14249
|View full text |Cite
|
Sign up to set email alerts
|

Linseed oil in boar's diet improved in vivo fertility and antioxidant status

Abstract: The reactive oxygen species (ROS) which are produced during storage of boar semen are causing oxidative stress and leads to poor fertility. Also, tropical and sub-tropical weather condition adversely impacts the physicomorphological quality and fertility of boar sperm. The aim of this study was to examine the effects of feeding linseed oil to boar on its seminal attributes, sperm kinetics, biomarkers of antioxidant, fatty acid profile of seminal plasma (SP) and sperm and in vivo fertility. Six Hampshire crossb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 64 publications
2
6
0
Order By: Relevance
“…This is the first report of the application effects of EELO on boar semen quality which shows its positive effects on reproduction parameters. Previous data have [ 6 , 7 , 8 , 9 , 10 ] shown that the application of different sources of PUFAs in boar diets significantly increased semen volume, total sperm pen ejaculate and sperm concentration, in addition to reducing reaction time. This may be due to the ability of PUFAs to affect many factors which are related to the synthesis and metabolism of essential reproductive hormones, such as testosterone and prostaglandin [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is the first report of the application effects of EELO on boar semen quality which shows its positive effects on reproduction parameters. Previous data have [ 6 , 7 , 8 , 9 , 10 ] shown that the application of different sources of PUFAs in boar diets significantly increased semen volume, total sperm pen ejaculate and sperm concentration, in addition to reducing reaction time. This may be due to the ability of PUFAs to affect many factors which are related to the synthesis and metabolism of essential reproductive hormones, such as testosterone and prostaglandin [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers [ 6 , 7 , 8 , 9 , 10 , 41 , 42 , 43 ] have reported an increase in the total number of sperm in boars consuming supplements containing omega-3 fatty acids. What is more, they indicated that the application of dietary supplements increased the duration of ejaculation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations